Treatment patterns and medication adherence among newly diagnosed patients with migraine: a drug utilisation study - Valentina Orlando; Sara Mucherino; Valeria Marina Monetti; Ugo Trama; Enrica Menditto (BMJ Open)
Objectives Prophylactic drugs currently used for migraine treatment are not specific. Furthermore, few studies in existing literature describe drugs utilisation patterns and adherence to migraine prophylactic treatment. This study is aimed to describe utilisation patterns of migraine drugs, evaluate adherence to prophylactic medications and investigate drug-related costs.Design Retrospective population-based study using an administrative health-related database.Setting Primary care setting in the Campania region, Southern Italy.Participants This study was carried out between 1 January 2016 and 31 December 2018, involving 12 894 subjects with any primary or secondary hospital discharge with migraine diagnosis, or at least two medical dispensations of migraine-specific acute or prophylactic medications (triptans or pizotifen). Subjects were classified into four treatment cohorts: no treatment, acute, prophylactic and both acute and prophylactic. Subjects were followed-up for 1 year.Outcome measures Utilisation patterns of migraine drugs at treatment initiation; adherence to prophylactic treatment; discontinuation, restart and switching rates; annual migraine drug costs per patient.Results Overall, 81.1% of subjects received acute treatment as their initial migraine treatment regimen, 10.7% prophylactic treatment, 8.2% both acute and prophylactic treatment. 599 patients were treated prophylactically; of these, 26.2% adhered to their initial treatment while 73.8% reported interruptions in treatment. Among the latter, 46.4% of patients discontinued the treatment completely within 103 days (IQR 89.0), 31% restarted treatment 46 days after interruption (IQR 60.0) and 22.6% switched to another treatment within 98 days (IQR 57.5) (p<0.001). The median annual cost of drugs per patient was €103 for those treated acutely, €75 for those treated prophylactically, €163 for those treated both.Conclusions Migraine treatment with acute medications is still prevalent in Italy; only few patients received prophylactic treatment with poor adherence to treatment. These findings reflect an unmet need for improved prophylactic therapies in order to provide a better disease management.